The Influence of Transformational Leadership and Work Motivation on Employee Well-Being and Performance Improvement at BUMDes Pamekasan - Moh. Jauhari Ibrahim; Samsuki (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of transformational leadership and work motivation on employee well-being and performance at BUMDes in Pamekasan using a qualitative approach. Findings from interviews, observations, and document analysis show that leaders who inspire, model positive behavior, and foster innovation enhance intrinsic motivation. This motivation supports employees’ psychological, social, and economic well-being, leading to greater productivity, commitment, and service quality. The study highlights transformational leadership and motivation as key, interrelated factors in improving employee outcomes, with implications for sustainable governance and the development of BUMDes organizations.